The Management of International Tourism / Second Edition - Brooke Michael Z; Buckley Peter J; Witt Stephen F (Rouledge, 1995)
The authors in this book clearly explain key business concepts and how they apply to the management of international tourism businesses. Preface, The Environment of International Tourism, The International Tourism Industry, Tourism Demand, Methods of Operation, The International Marketing of Tourism, Finance and Control, Organization and Staffing, Research and Innovation, Corporate Strategies for International Tourism, International Tourism: The Future, References.